Influence of Serum Levels of Thyroid-Stimulating Hormone and Anti-Thyroid Peroxidase Antibodies, Age and Gender on Depression as Measured by the Zung Self-Rating Depression Scale - Shinkov, Alexander D.; Borisova, Anna-Maria I.; Kovacheva, Russanka D.; Vlahov, Yordan D.; Dakovska, Lilia N.; Atanassova, Iliana D.; Petkova, Polina L.; Aslanova, Nina L.; Vukov, Mircho I. (Folia medica (Plovdiv), 2014)
The AIM of the present study was to explore the level of depression in the respondents using the Zung self-rating depression scale (SDS) and find a correlation with the levels of the thyroid-stimulating hormone (TSH) and the anti-thyroid peroxidase antibodies (anti-TPO), the age and gender of the participants. PATIENTS AND METHODS: 2401 subjects aged 20-84 yrs were included, 1344 of them female aged 48.7 ± 14.4 yrs and 1057 male, aged 46.5 ± 14.5 yrs (p < 0.001). All participants completed the Zung SDS questionnaire and a depressive score was calculated and interpreted as follows: less than 49 points - no depression, between 50 and 59 points - mild depression, between 60 and 69 points - moderate depression and more than 69 points - severe depression. Body height and weight were measured and serum TSH and Anti-TPO were determined. RESULTS: SDS was higher in the females (47.6 ± 9.7 vs. 41.7 ± 8.6, p < 0.001) and correlated with the subjects’ age (Spearman’s ρfemale = 0.447, p < 0.001, ρmale = 0.402, p < 0.001). Depression was more prevalent in the females (all p < 0.001) with hypothyroidism than in the euthyroid subjects (odds ratio 1.8, 95% CI 1.15-2.80, p < 0.011). The odds ratio for depression was 3.47 (2.64-4.57) for the female gender and the risk of depression increased by 6% (5 - 7) with each added year of age. The anti-TPO, BMI and waist circumference did not influence the regression models. CONCLUSION: The depressive score was higher in the females and increased with age. Hypothyroidism determined a higher risk of depression in the females ЦЕЛЬ: Настоящее исследование ставит себе целью исследовть уровень депрессивности участников посредством вопросников самооценки Zung-а и найти связь с уровнями ТСГ и антитиреопероксидазных антител (анти-ТПО), с возрастом и полом участников. ПАЦИЕНТы И МЕТОДЫ: Включены 2401 человек в возрасте от 20 до 84 лет; 1344 женщины в возрасте 48.7 ± 14.4 г. и 1057 мужчин в возрасте 46.5 ± 14.5 г. (p < 0.001). Пополнен вопросник самооценки Zung-а. Интерпретация результатов следующая: до 49 очков - отсутствие депрессии, от 50 до 59 - легкая депрессия, от 60 до 69 - умеренная депрессия, свыше 70 - тяжелая. Измерены рост, масса тела, окружность талии и ТСГ и Анти-ТПО антитела. РЕЗУЛЬТАТЫ: Депрессивный скок оказался более высоким у женщин по сравнению с мужчинами (47.6 ± 9.7 - 41.7 ± 8.6, p < 0.001), и коррелировал с возрастом (Spearman’s ρж. = 0.447, p < 0.001, ρм. = 0.402, p < 0.001). Частотата депрессии более высокая у женщин (все p < 0.001) и более высокая у тех с гипертиреоидизмом по сравнению с женщинами с эутиреодизмом /отношение шансов 1.8, 95% ИД 1.15 - 2.80 р < 0.011/. Отношение шансов появления депрессии у женщин по сравнению с мужчинами 3.47 (2.64 - 4.57), а риск нарастает приблизительно на 6% (5 - 7) на каждый год увеличения возраста. Анти-ТПО, ИТМ и окружность талии не оказывают влияние в модели. ЗАКЛЮЧЕНИЕ: Депрессивность